Rancang Bangun Media Pembelajaran Interaktif Berbasis Website pada Program Studi Permesinan Poltekpel Barombong - Dewi Apriani, Dahlia; Ihsan, Fahri; Achmadita, Arnaldy; Irwan Kurnia, M. Alda; Zaman, Baizul (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This study aims to develop an interactive web-based learning media to enhance students' understanding of ship construction and stability in the Marine Engineering program. The media was designed using use case diagrams, activity diagrams, and mockups, then validated by media and subject matter experts. Validation results showed high feasibility, with respective scores of 98.8% and 89.6%. This media supports more flexible and interactive learning while preparing students to meet the demands of the maritime industry..